2021
DOI: 10.2903/j.efsa.2021.6846
|View full text |Cite
|
Sign up to set email alerts
|

Safety of mung bean protein as a novel food pursuant to Regulation (EU) 2015/2283

Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens ( NDA ) was asked to deliver an opinion on mung bean protein as a novel food ( NF ) pursuant to Regulation ( EU ) 2015/2283. The NF , which is the subject of the application, is mung bean protein extracted from seeds of the plant Vigna radiata . The NF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Nevertheless, EFSA noted that the cumulative exposure to magnesium (background dietary intake + intake of NF at proposed use) would exceed the adequate intake (i.e., 300–350 mg/day) in adults and the sodium content (i.e., 7320–12,200 mg/kg) would exceed the safe levels of intake (i.e., 2.0 g/ day in adults). However, it was concluded that these levels can already be exceeded with the background diet (Turck et al., 2021a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, EFSA noted that the cumulative exposure to magnesium (background dietary intake + intake of NF at proposed use) would exceed the adequate intake (i.e., 300–350 mg/day) in adults and the sodium content (i.e., 7320–12,200 mg/kg) would exceed the safe levels of intake (i.e., 2.0 g/ day in adults). However, it was concluded that these levels can already be exceeded with the background diet (Turck et al., 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…The protein content of raw legumes average 25 g/100 g edible product and reaches up to 90% in protein isolate and concentrates (used for analogues) (Table 1) (Boukid & Castellari, 2022; FAO, 2016). In Europe, legume consumption has a long history; among those included in this review, mung bean protein received “novel food (NF)” authorization from the European Food Safety Authority (EFSA) in 2021 (Turck et al., 2021a). Legumes already employed in analogues are faba bean in meat‐ and fish‐analogues (beyondmeat.com; goodcatchfoods.com), mung bean in egg‐analogues (zeroegg.com), and lentils in dairy‐ and fish‐analogues (violifefoods.com; goodcatchfoods.com).…”
Section: Methodsmentioning
confidence: 99%
“…However, certain plant‐derived proteins are considered new in the West. For example, mung bean protein is considered as a novel food by the European Union (EU) (Turck et al., 2021). A determination on whether a plant‐derived protein product is a new or novel food may be made based on the extent of processing as well as increased dietary exposure to certain plant components (including any contaminants that may be present) in the plant protein concentrate compared to the unprocessed plant.…”
Section: Nfps Food Safety Considerationsmentioning
confidence: 99%
“…4 It is a good source of protein, which is easily digestible and provides most essential amino acids. 5 Different food products from mung bean evolved, such as sweets, snacks, and savoury items in India, cakes, noodles, and soups in China, and fresh bean sprouts in America and Europe. 5,6 Furthermore, mung bean is considered as a functional food that benefits our health beyond basic nutrition.…”
mentioning
confidence: 99%
“…5 Different food products from mung bean evolved, such as sweets, snacks, and savoury items in India, cakes, noodles, and soups in China, and fresh bean sprouts in America and Europe. 5,6 Furthermore, mung bean is considered as a functional food that benefits our health beyond basic nutrition. Recent studies identified hypolipidemic, hypoglycemic, antioxidative, liver-protective, and neuroprotective potential of the mung bean.…”
mentioning
confidence: 99%